2021
DOI: 10.1021/acsami.1c12854
|View full text |Cite
|
Sign up to set email alerts
|

Tuning Surface States of Metal/Polymer Contacts Toward Highly Insulating Polymer-Based Dielectrics

Abstract: Metal−polymer interface plays a crucial role in controlling the dielectric performance in all flexible electronics. Ideally, the formation of the Schottky barrier due to the large band offset of the electron affinity of the polymer over the work function of the electrode should sufficiently impede the charge injection. Arguably, however, such an injection barrier has hardly been indisputably verified in polymer−metal junctions due to the everexisting surface states, which dramatically compromise the barrier th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 41 publications
(63 reference statements)
1
31
0
Order By: Relevance
“…While the key point of this study is the deep potential located in the BN coating layer, other experiments such as photocurrent injection measurement can also provide complementary information such as barrier height between the electrode and the polymer as well as the surface states. A recent study of hBN using photocurrent injection measurements has indeed showed the ability of hBN nanocoats to reduce surface states at polymer−metal interfaces, 40 further corroborating the carrier trapping reported here.…”
Section: ■ Conclusionsupporting
confidence: 87%
“…While the key point of this study is the deep potential located in the BN coating layer, other experiments such as photocurrent injection measurement can also provide complementary information such as barrier height between the electrode and the polymer as well as the surface states. A recent study of hBN using photocurrent injection measurements has indeed showed the ability of hBN nanocoats to reduce surface states at polymer−metal interfaces, 40 further corroborating the carrier trapping reported here.…”
Section: ■ Conclusionsupporting
confidence: 87%
“…The polymer-based dielectrics must withstand ever-increasing and enormous operating electric fields, but a clear negative correlation between U e and E b of surface states in polymer dielectrics has been demonstrated experimentally ( Wang et al., 2021 ). The surface state dramatically reduces the charge injection barrier height lead to high electrical conduction.…”
Section: Micro-/macro-surface and Interface Engineering For Polymer D...mentioning
confidence: 99%
“…Epoxy resin (EP) is widely used in the insulation of electrical equipment and electronic devices. However, the distortion of the electric field induced by space charge injection caused by high field and temperature gradient aggravates the breakdown and electrical tree of insulation materials [ 1 , 2 , 3 , 4 ], which seriously threatens the safe and stable operation of power equipment. Therefore, it is urgent to study high-performance direct current insulation materials.…”
Section: Introductionmentioning
confidence: 99%